Overcoming the lack of oral availability of cyclic hexapeptides: design of a selective and orally available ligand for the integrin alpha v beta 3 - Weinmueller, Michael; Rechenmacher, Florian; Marelli, Udaya Kiran; Reichart, Florian; Kapp, Tobias G.; Raeder, Andreas F. B.; Di Leva, Francesco Saverio; Marinelli, Luciana; Novellino, Ettore; Munoz-Felix, Jose M.; Hodivala-Dilke, Kairbaan; Schumacher, Adi; et al. (Angewandte Chemie-International Edition, 2017)
Ahighly systematic approach for the development of both orally bioavailable and bioactive cyclic N-methylated hexapeptides as high affinity ligands for the integrin alpha v beta 3 is based on two concepts: a) screening of systematically designed libraries with spatial diversity and b) masking of the peptide charge with a lipophilic protecting group. The key steps of the method are 1) initial design of a combinatorial library of Nmethylated analogues of the stem peptide cyclo(d-Ala-Ala(5)); 2) selection of cyclic peptides with the highest intestinal permeability; 3) design of sublibraries with the bioactive RGD sequence in all possible positions; 4) selection of the best ligands for RGD-recognizing integrin subtypes; 5) finetuning of the affinity and selectivity by additional Ala to Xaa substitutions; 6) protection of the charged functional groups according to the prodrug concept to regain intestinal and oral permeability; 7) proof of biological effects in mice after oral administration.